The Conservation And Preservation Of Perak Man From Gua Gunung Runtuh Site In Lenggong, Perak , Malaysia. - Chia, Assoc Prof. Dr. Stephen, Ming Soon; Majid, Zuraina (2002)

(untitled)
In 1990-91, archaeological excavations were conducted at Gua Gunung Runtuh in Lenggong, Perak by Professor Zuraina Majid and her team from the Centre For Archaeological Research Malaysia, Universiti Sains Malaysia, Penang. The excavations uncovered a primary burial of a 10,000-11,000 year old human skeleton (Zuraina Majid 1994). This skeleton was named "Perak Man" as it was found in the state of Perak in Malaysia.